Neoproterozoic U–Pb (zircon) and ⁴⁰Ar/³⁹Ar (muscovite) ages from granitic pegmatite clasts, basal Ross Island Formation, Grand Manan Island, New Brunswick, Canada - Barr, Sandra M.; Mortensen, James K. (Atlantic Geoscience, 2019)
Zircon grains from a granitic pegmatite clast from conglomerate at the base of the Ross Island Formation on Grand Manan Island indicate an igneous crystallization age of 664.1 ± 4.6 Ma. The clast also contains abundant older inherited grains back to the Archean. Muscovite in the same clast and an additional similar clast yielded cooling ages of 607.0 ± 3.7 Ma and 619.6 ± 4.1 Ma, respectively, providing a maximum depositional age for the host conglomerate of the Ross Island Formation. The similarity in age to pegmatite in the Seven Hundred Acre Island Formation in Penobscot Bay, Maine, supports earlier correlations between the two areas based on similarities in Neoproterozoic quartzite and carbonate units.